Organization and Education Development Reflecting and Transforming in a Self-Discovery Journey - Nanwani, Suresh (Routledge Studies in Leadership, Work and Organizational Psychology, 2021)
"Organization and Education Development combines reflective thinking and practice, action research living theory, and organization development to explore the self-discovery of meaning and purpose. It charts a journey undertaken by the author in pursuit of professional development through self-awareness and self-change as a fully integrated person and a better professor. This book is about an individual's integrative journey of self-discovery. The author's narrative includes values and organizational development concepts and theories shared with fellow travelers, including supervisors, friends, and students. He shares invaluable insights and examples with the reader, using a model of a six-spoke wheel of final discovery and the MICAI intersection model. These integrative guides provide examples on how to search for what is best in everyday life and what gives us true meaning, encouraging personal reflection and ways of nurturing appreciation for our own lives. This multidisciplinary book combines western and eastern models and philosophies and draws from organization development, positive psychology, and education development. It will be ideal reading for students, researchers, and academics in the fields of organizational development, organizational psychology, social psychology, and education. It will appeal to any reader interested in learning about self-development. "